2020
DOI: 10.7717/peerj.10130
|View full text |Cite
|
Sign up to set email alerts
|

Serum uric acid level is correlated with the clinical, pathological progression and prognosis of IgA nephropathy: an observational retrospective pilot-study

Abstract: Objectives This study was aimed to assess the relationship between serum uric acid (SUA) level and the clinical, pathological phenotype of IgA nephropathy (IgAN), and to determine the role of SUA level in the progression and prognosis of IgAN. Methods A total of 208 patients with IgAN were included in this study, and were classified into the normo-uricemia group and hyperuricemia group according to the SUA level. The clinical data at baseli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…Hyperuricemia may cause changes in renal structure through different biological mechanisms, such as endothelial dysfunction, glomerulosclerosis, and tubulointerstitial renal damage, which eventually lead to an irreversible decline in kidney function 23‐26 . Recent studies also have shown that hyperuricemia patients had higher T scores than normal uricemia patients 27 . The HUA leads to tubular atrophy/interstitial fibrosis might be illuminated by the following mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyperuricemia may cause changes in renal structure through different biological mechanisms, such as endothelial dysfunction, glomerulosclerosis, and tubulointerstitial renal damage, which eventually lead to an irreversible decline in kidney function 23‐26 . Recent studies also have shown that hyperuricemia patients had higher T scores than normal uricemia patients 27 . The HUA leads to tubular atrophy/interstitial fibrosis might be illuminated by the following mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“… 23 , 24 , 25 , 26 Recent studies also have shown that hyperuricemia patients had higher T scores than normal uricemia patients. 27 The HUA leads to tubular atrophy/interstitial fibrosis might be illuminated by the following mechanisms. Urate crystals sedimentate in the renal tubules can directly block or damage the renal tubules and also form uric acid renal stones to damage the kidney, which makes for renal tubular atrophy and interstitial fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Through full-text reviews, two conference abstracts, two duplicated data-contained articles, and two articles without enough data to estimate the HR were removed from the remaining 15 articles. Finally, we included nine studies with 10,006 patients [ 10 , 14–18 , 23–25 ] ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In Table 1 , among the nine studies, eight were performed in Asian countries: China, Korea, and Japan [ 10 , 14–16 , 18 , 23–25 ], and one was performed in Western countries (Turkey) [ 17 ]. Six of the nine studies estimated the correlation between the decreasing Hb in serum and kidney disease progression in IgAN [ 14–18 , 23 ], in which the HR was calculated using continuous variables relative to 1 g/dL.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Scr indicator was not included in the model too. In the previous literatures [3,20], Scr index was included in the original form. In order to explain the relationship between Scr level and hyperuricemia more conveniently, we transformed the original numerical variable into a categorical variable.…”
Section: Discussionmentioning
confidence: 99%